Chia (Salvia hispanica L.) oil extraction: Study of processing parameters - Martinez, Marcela Lilian (2012)
The processing parameters related with chia oil extraction employing screw press have not been studied yet. A Box–Behnken experimental design was used to study the optimization process by response surface analysis. The independent variables considered were seed moisture content, restriction die, screw press speed and barrel temperature, while the response variables measured were oil yield, fines content in oil and oil quality (acidity, peroxide index, K232, K270, values, antioxidant activity and total tocopherol content). Since chemical quality data of chia seeds oil pressed at different conditions was not affected, the response was optimize to maximize oil yield. The results suggested that 0.113 g/g dry solids (0.101 g/g seed), 6 mm restriction die, 20 rpm screw press speed and 30 °C barrel temperature were the best processing combination to maximize oil yield.